Galactosylated poly(ethylene glycol)-b-poly (l-lactide-co-β-malic acid) block copolymer micelles for targeted drug delivery: preparation and in vitro characterization - Suo, Aili (Dove Medical Press, 2010)
Biodegradable galactosylated methoxy poly(ethylene glycol)/poly(l-lactide-co-β-malic acid) (Gal-PEG-b-PLMA) block copolymer micelles were successfully prepared by a solvent diffusion method, and could efficiently encapsulate doxorubicin. The Gal-PEG-b-PLMA micelles before and after doxorubicin loading were characterized by size, morphology, in vitro drug release, and in vitro cytotoxicity in HepG2 cells. Transmission electron microscopy and dynamic light scattering results showed that the empty and doxorubicin-loaded micelles were approximately spherical in shape and had mean sizes of about 72 nm and 85 nm, respectively. In vitro release behavior of doxorubicin from the micelles was pH-dependent, with obviously faster release rates at mildly acidic pH 4.5 and 5.5 compared with physiologic pH 7.4. Methylthiazoletetrazolium assay and flow cytometric analysis indicated that the doxorubicin-loaded galactosylated micelles exhibited a greater growth-inhibitory effect on HepG2 cells than the nongalactosylated doxorubicin-loaded micelles, and induced S phase cell cycle arrest. Confocal laser scanning microscope observations revealed that the galactosylated micelles could be efficiently internalized by HepG2 cells through receptor-mediated endocytosis. The results suggest that Gal-PEG-b-PLMA copolymer micelles are a promising carrier system for targeted drug delivery in cancer therapy.